2020
DOI: 10.3389/fcell.2020.563509
|View full text |Cite
|
Sign up to set email alerts
|

Placenta-Derived Osteoprotegerin Is Required for Glucose Homeostasis in Gestational Diabetes Mellitus

Abstract: Osteoprotegerin (OPG) is involved in various biological processes, including bone remodeling, vascular calcification and pancreatic β-cell function. Although some clinical studies have shown an increase in serum OPG level during pregnancy, the role of OPG in gestational diabetes mellitus (GDM) is largely unknown. Therefore, we explored the effect of OPG in metabolic homeostasis during pregnancy. We initially evaluated serum OPG levels using ELISA and western blotting techniques on samples from GDM patients. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Retrospective clinical studies showed that the circulating levels of OPG in women with a history of GDM were significantly increased compared to normal women later in life, and they were positively correlated with various metabolic diseases with a high incidence later in life ( Akinci et al, 2011 ; Telejko et al, 2015 ). We also have proven that placenta-derived OPG could regulate β-cell proliferation and glucose metabolism in placental glucose involved in glucose homeostasis in pregnant mice ( Huang et al, 2020 ). OPG could promote glucose homeostasis during pregnancy, while there is no direct evidence to prove that OPG regulates hypertension during pregnancy.…”
Section: Osteoprotegerin Attenuated Symptoms In Gestational Diabetes ...mentioning
confidence: 89%
See 1 more Smart Citation
“…Retrospective clinical studies showed that the circulating levels of OPG in women with a history of GDM were significantly increased compared to normal women later in life, and they were positively correlated with various metabolic diseases with a high incidence later in life ( Akinci et al, 2011 ; Telejko et al, 2015 ). We also have proven that placenta-derived OPG could regulate β-cell proliferation and glucose metabolism in placental glucose involved in glucose homeostasis in pregnant mice ( Huang et al, 2020 ). OPG could promote glucose homeostasis during pregnancy, while there is no direct evidence to prove that OPG regulates hypertension during pregnancy.…”
Section: Osteoprotegerin Attenuated Symptoms In Gestational Diabetes ...mentioning
confidence: 89%
“…RANKL can bind to RANK on neighboring cells and activate NF-κB signaling to regulate biological processes, such as the cell cycle, proliferation, differentiation, and apoptosis ( Blomberg Jensen et al, 2021 ). RANKL is involved in regulating many processes, such as immune surveillance, bone resorption, monocyte chemotaxis, fibrosis, β-cell proliferation, and glucose homeostasis ( Bernardi et al, 2016 ; Huang et al, 2020 ). RANKL can be found in membrane-bound and soluble forms, in which RANKL binds to two other RANKL molecules to form a trimer that binds to the receptor RANK ( Rinotas et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…MSTN , a negative regulator of muscle development, may also be involved in cytokine production and glucose metabolism, and has been associated with preeclampsia and IUGR in human pregnancies [ 36 , 37 ]. TNFRSF11B , also known as osteoprotegerin, is a secreted factor that is a key regulator in bone metabolism, but is also pro-angiogenic, and has been associated with preeclampsia and diabetes mellitus in human pregnancies [ 38 , 39 ]. WNT9B drives mesenchymal–epithelial transitions in the urogenital system during organogenesis [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Total RNA was isolated by the previous description ( Huang et al, 2020b ) using the TRIzol reagent (10296010, Invitrogen) and quantified using a NanoVueTM Plus Spectrophotometer (GE Healthcare, Buckinghamshire, United Kingdom). The A260/A280 ratio of the optical density was measured using the NanoVueTM Plus Spectrophotometer.…”
Section: Methodsmentioning
confidence: 99%